Men's belief in sexual myths and factors effecting these myths [Erkeklerde cinsel mitlere inanma oranlari ve mitlere inanmayi etkileyen faktörler] - (:unkn) unknown (Kare Publishing, 2011)
Objective: Sexual myths are often exaggerated, incorrect and unscientific ideas on sexuality that people believe to be true. The aim of this study is to determine the acceptance rate of common sexual myths and related factors among men. Method: Data was collected from 167 voluntary males (18-67 years). A structured interview including sociodemographic characteristics and sexual myth questionnaire investigating 30 common sexual myths was carried out with the participants. Result: There are numerous myths regarding sexuality in our study population. It was found that marital status, educational level, region lived until adolescence (sub-district and village or province and district), first source for sexual information and result of the first sexual relationship influence rates of belief for sexual myths. Conclusion: High levels of belief in sexual myths among males in our study group can be interpreted as a result of inadequate sexual education in the society. We believe that further larger scale population studies might be beneficial for planning sexual education in our society.
Keywords: Myths; Sexual knowledge; Sexuality